DNA barcode of Metroxylon sagu and others palm species using matK gene - Barahima Abbas; RUDY JOHANIS KABES; NOUKE LENDA MAWIKERE; Reymas Marten Reinhard Ruimassa; RUDY APRIANTO MATURBONG (Society for Indonesian Biodiversity, 2020)
Abstract. Abbas B, Kabes RJ, Mawikere NL, Ruimassa RMR, Maturbong RA. 2020. DNA barcode of Metroxylon sagu and other palm species using matK gene. Biodiversitas 21: 4047-4057. Palm family encompasses numerous species, and they disperse broadly across tropical and subtropical countries. The palm family is generally used as an ornamental plant, food, oil, and industrial raw materials. Species of palm that accumulate large amount carbohydrate in the trunk is sago palm (Metroxylon sagu Rottb). The objectives of this study were to explore the plastid sequence associated with matK genes in the palm family and to reveal DNA barcode of 16 genera and 28 species of the palm. Plant materials used in the studies were derived from Sago Research Center (SRC), and other palm sequences were retrieved from the GenBank, NCBI accessions. The PCR product was sequenced by the 1st Base Asia, Singapore. Sequences of the matK gene that were observed in the plastid genome of M. sagu were registered into the NCBI GenBank as DNA barcode of M. sagu. Percent query cover of Blast analysis range from 98% to 100%, and identity range from 97.70% to 100%. Plastid nucleotides associated with matK genes in the chloroplast genome of palm family were shown substantial differences in inter-genera and small differences in inter-species. Genetic distance among palm family range from 0 to 0.026 with nucleotide variation observed was of 0.008822 value. The result of molecular phylogenetic analysis showed that the palm family separated into three clades and three sub-clades based on the plastid matK gene. Species of M. sagu and M. warburgii were considered closely related as compared to other palm species. The matK gene barcoding method is one powerful tool for identification inter-genera and inter-species of the palm.